2020
DOI: 10.1177/1120672120904667
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings and outcomes of uveitis associated with multiple sclerosis

Abstract: Purpose: To describe the clinical findings and outcomes in patients who presented with uveitis associated with multiple sclerosis. Methods: Retrospective review of 20 patients (38 eyes). Results: The most frequent ocular finding was multifocal elongated retinal perivenous “sheathing” with focal vascular leakage on fundus fluorescein angiography in 29 eyes followed by vitreous snowballs and debris in 26 eyes, anterior chamber inflammation in 15 eyes, mutton-fat keratic precipitates in 14 eyes, posterior synechi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…All of the former patients had presented with intermediate uveitis along with a range of signs, including anterior uveitis, posterior uveitis, and vasculitis. These findings correlate with the reports in the literature that the most common type of uveitis in MS is intermediate uveitis that primarily involves the vitreous, peripheral retina, and pars plana [ 8 , 10 , 11 ]. The ocular inflammation may develop concurrently, prior to, or after the development of the neurological signs and symptoms, but none of the earlier studies had identified any major difference in the clinical features of MS patients with and without uveitis [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…All of the former patients had presented with intermediate uveitis along with a range of signs, including anterior uveitis, posterior uveitis, and vasculitis. These findings correlate with the reports in the literature that the most common type of uveitis in MS is intermediate uveitis that primarily involves the vitreous, peripheral retina, and pars plana [ 8 , 10 , 11 ]. The ocular inflammation may develop concurrently, prior to, or after the development of the neurological signs and symptoms, but none of the earlier studies had identified any major difference in the clinical features of MS patients with and without uveitis [ 12 ].…”
Section: Discussionsupporting
confidence: 90%
“…Patients with SS experience BRAO, which is not a characteristic feature of MS; thus, this is a differentiating symptom which should be sought for in FA when the diagnosis of SS is suspected, even in patients without visual symptoms, or when the examination of the fundus of the eye seems normal [2,12]. In the case of uveitis during MS, the change most frequently observed in FA is multifocal elongated retinal perivenous 'sheathing' with focal vascular leakage [62]. AWH at the site of BRAO is non-specific for SS, and should also be an incentive for the consideration of the presence of other factors responsible for the development of vessel inflammation.…”
Section: Ss or Ms-differentiationmentioning
confidence: 99%
“…1 ). Enhanced-depth imaging OCT (OCT-EDI) better visualises choroidal structures, [ 18 ] and changes in choroidal thickness can relate to posterior uveitis [ 19 , 20 ]. OCT angiography (OCT-A), non-invasively images perfused retinal and choroidal vessels of the central macula [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%